Effect of Temperature on Kerogen Transformation and Hydrocarbon Generation in Bazhenov Formation (Western Siberia, Russia) Rocks During Hydrous Pyrolysis - Grigorii G. Savostin; Margarita S. Tikhonova; Anton G. Kalmykov; Dmitry S. Volkov; Mariia O. Kostyshina; Olesya N. Vidishcheva; Mariia L. Makhnutina; Yuliya A. Kotochkova; Tatiana V. Grigorenko; Mikhail A. Proskurnin (Energies)
The aim of this investigation is to determine the role of temperature in hydrocarbon generation in Bazhenov formation source rocks, as hydrothermal processes in situ are supposed to be the main contributor to kerogen transformation in Western Siberia. Laboratory modeling of organic matter isothermal transformation in powdered and extracted samples by hydrous pyrolysis at 300 °C, 325 °C, 350 °C, 375 °C, and 400 °C for 24 h was performed. Heated samples were analyzed via pyrolysis, and hydrocarbons were investigated by GC and GC-MS. Results show that more than 90% of the kerogen generation potential was utilized. The amounts of liquid and gaseous products reached 82 and 126 mg of hydrocarbon/g TOC, respectively. The volume of generated gas increased while the maximum production of liquid decreased with temperatures over 350 °C. The biomarker composition of liquid products at different temperatures was similar. The characteristics of kerogen and the product composition had a high correlation with the parameters for samples naturally formed in situ under an elevated heat flow. More subtle chemical analyses are required to determine the effects of kerogen’s chemical structure and the rock mineral composition on oil and gas generation.